The Hairdresser of Harare, Questioning Gender and Sexuality in a Zimbabwean Novel - Pierre Leroux (Itinéraires)
As gay characters have been rather rare in Zimbabwean literature, Tendai Huchu’s first novel, The Hairdresser of Harare attracted a lot of attention when it was published in 2010. The story of Vimbai, a single mother who dreams of owning her own salon, and Dumisani, her friend who tries to hide his sexual preferences, thus works as a catalyst to explore different aspects of a society in crisis. For those reasons, the author has been both praised and criticized. In this article, I argue that, in the novel, the depiction of homosexuality is closely related to the exploration of popular literary genres such as the romance novel. The subversion of “chick lit,” for instance, allows Tendai Huchu to question fixed gender categories and sexuality. The author reveals the violence Dumisani undergoes by using several conflicting narratives that try to depict and analyze homosexuality.